2013
DOI: 10.1063/1.4796099
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon resonances and the plasmon-induced field enhancement in nanoring dimers

Abstract: Plasmon resonances and the plasmon-induced field enhancement (FE) in sodium nanoring dimers are investigated by time-dependent density functional theory. For larger separations, the optical absorption, the induced charge response and the frequency dependent current demonstrate that there are two capacitive coupling plasmon modes. One feature of FE is that, in the surface region of the nanoring, it has a very large maximum. Another feature of FE is that, along the perpendicular bisector of the line segment join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several concepts such as hybridization, Fano resonances, and Rabi splitting have been successfully transferred from atomic and molecular physics to describe analogue phenomena seen in plasmonic systems. In the strong coupling regime, , the coupling between a molecular exciton and a plasmonic cavity results in anticrossings of the hybrid plexciton dispersion curves and the formation of two hybrid energy states separated by a Rabi splitting energy. More recently, dynamic tuning , and ultrafast manipulation ,, of the plexcitonic coupling have been investigated in such hybrid nanostructures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several concepts such as hybridization, Fano resonances, and Rabi splitting have been successfully transferred from atomic and molecular physics to describe analogue phenomena seen in plasmonic systems. In the strong coupling regime, , the coupling between a molecular exciton and a plasmonic cavity results in anticrossings of the hybrid plexciton dispersion curves and the formation of two hybrid energy states separated by a Rabi splitting energy. More recently, dynamic tuning , and ultrafast manipulation ,, of the plexcitonic coupling have been investigated in such hybrid nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that coupling between elementary excitations can be mediated by the near-field and in particular by the highly enhanced electric field near the surfaces of plasmonic nanostructures, known as “hot spots”. The strong and localized field in a plasmonic hot spot enhances the interaction between LSPRs and the local excitons, much as it enhances other molecular excitations. Plasmonic dimers are the canonical geometry for the generation of high-intensity hot spots, where the local field is sufficient to give rise to surface enhanced Raman spectroscopy at the single molecule level .…”
Section: Resultsmentioning
confidence: 99%